Green taxes: Environment, employment and growth. A computable general equilibrium analysis for Italy - Maurizio Bussolo; Dino Pinelli (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we investigate the potential costs and benefits of a comprehensive green fiscal reform in Italy. Using a Computable General Equilibrium (CGE) model for the country, we simulate scenarios of progressive reduction of emissions for 13 polluting substances. It is shown that the introduction of a tax targeted to one single pollutant, decreases not only the directly targeted emissions but also those of other pollutants. Besides the green tax costs, in terms of increased distortions and forgone production and welfare, are shown to be quite low. This important result depends on the assumption of a certain degree of flexibility in the production processes that allows polluters to switch to cleaner technologies when the tax is implemented. This assumption closely reflects observed economic behaviour especially when a decade or more is the period of analysis, as in our case. Finally, when green taxes revenues are used to reduce wage taxes, in a revenue neutral fiscal swap, a positive employment double dividend emerges.
Keywords: D5; H2; J3; 330; Green taxes; double dividend; CGE models; Ökosteuer; Allgemeines Gleichgewicht; Umweltschutz; Beschäftigung; Wirtschaftswachstum; Italien